FHY3 and FAR1 Act Downstream of Light Stable Phytochromes - Siddiqui, Hamad; Khan, Safina; Rhodes, Bruce M.; Devlin, Paul F. (Frontiers in Plant Science, 2016)
FHY3 and FAR1 are positively-acting transcription factors that directly regulate expression of a number of target genes in Arabidopsis thaliana. Here, we looked at the regulation of one specific target gene, ELF4. We demonstrate that the action of FHY3 and FAR1 in upregulation of ELF4 is light dependent. Furthermore, although FHY3 and FAR1 have been exclusively characterized as components of the phytochrome A signaling pathway because of their importance in regulating expression of phyA nuclear importers, we show that, as transcription factors in their own right, FHY3 and FAR1 act downstream of light stable phytochromes, phyB, phyD and phyE. We demonstrate that light stable phytochrome acts in a red / far-red reversible manner to regulate the level of FHY3 protein. We also observed that ELF4 shows specific FHY3 and FAR1-mediated light induction in the evening and we show that regulation by light stable phytochromes at this time is important as it allows the plant to maintain normal ELF4 expression beyond dusk when the day length shortens, something which would not be possible through light labile phytochrome action. Without FHY3 and FAR1, ELF4 expression falls rapidly at dusk and in short days this results in an early drop in ELF4 expression, accompanied by a de-repression of an ELF4 target gene later in the night. Our results, therefore, demonstrate an important role for FHY3 and FAR as mediators of light stable phytochrome signaling.